(untitled) (Comprehensive Journal of Science, 2026)
Both Italy and France had interests and ambitions in the Fezzan region of Libya. The reasons for this interest are: To European colonialism and the political and economic competition between the major powers at that time. In 1912 A D, Libya was occupied by Italy. And Fezzan was a strategic region for it. So Italy took advantage of Fezzan’s geographical location. Which is rich in natural resources. To enhance its influence and achieve its interests in Region. Haly region and regions surrounding him. As for France, it also had an interest in Qaran due to its geostrategic impact and the enormous wealth available in Al-Raqim. It sought to achieve economic gains in addition to expanding its colonial influence in Southern Libya, Events developed during. That period of modern Libya history was affected by the experiences of the two word wars. The colonial powers divided the country into areas of influence and long conflict until the political situation changed after word war II, when English control over Libya was transferred after 1943, and the region. Until it withdrew from the Quran in Tawfeer 1956. Therefore, this participation deal with Italian-French ambitions and the struggle for influence over Fezzan. This study was divided into two parts: This first section: Italian ambitions in the Fezzan region. The second topic: France’s colonial ambition in Libya and occupation of Fezzan.